Development of a Pretreatment Program to Improve Biological Treatability of High Strength and Toxic Industrial Wastewater - Brenner, A.; Belkin, S.; Abeliovich, A. (Water science and technology, 1994)
A biological treatment process has been suggested as the main treatment stage for a high (organic) strength industrial wastewater stream, discharged by several chemical industries within a large industrial park. Treatability studies have indicated that the wastes contain a fraction of toxic and non-biodegradable organic matter, which limits the implementation of a conventional biological treatment process for the combined wastewater stream. Therefore, an in-plant control program including waste segregation and process-specific pretreatments is proposed. A protocol that enables selection of waste streams amenable to biological treatment and identification of problematic streams requiring pretreatment is presented and demonstrated. It includes simplified laboratory procedures used for chemical and toxicological characterization of source streams originating in various processes. The results can be used for the development of a pretreatment program for problematic waste streams, based upon local small-scale solutions.